1986
DOI: 10.3109/10915818609141024
|View full text |Cite
|
Sign up to set email alerts
|

The Setting of Particulate Exposure Levels for Chronic Inhalation Toxicity Studies

Abstract: This paper briefly reviews the development of regulatory agency guidelines for toxicity testing and the impact of the maximum tolerated dose (MTD) concept on chronic study designs within and outside of the regulatory arena. From the orientation of an inhalation toxicologist, the MTD is viewed as a difficult and costly concept to implement and one that is generally inappropriate as a general basis for setting dust exposure levels in subchronic and chronic inhalation toxicity studies. Two possible alternatives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A broad discussion of this topic has been provided by Morrow (1986). The concept of the maximum tolerated dose (MTD) has been widely used in long-term bioassays.…”
Section: Discussionmentioning
confidence: 99%
“…A broad discussion of this topic has been provided by Morrow (1986). The concept of the maximum tolerated dose (MTD) has been widely used in long-term bioassays.…”
Section: Discussionmentioning
confidence: 99%
“…Expressed in terms of mass, overload has been reported to occur when burdens of a dust exceed 1 mg/g lung (Morrow, 1986). It has also been reported that volume, not mass, of phagocytized particles determines the extent of overloading (Morrow, 1988).…”
Section: Experimental Dust Overload (Intraluminal Dust Loading)mentioning
confidence: 97%
“…Morrow (1986aMorrow ( , 1986b noted that the classic MTD is inappropriate for inhalation studies of poorly soluble particles of low intrinsic toxicity, primarily because, unlike liquids or vapors, particles are retained within the target organ (lungs) and can overwhelm macrophage-mediated clearance, resulting in injury that is nonspecific to the particle composition. Pulmonary injury is indicated by accumulation of macrophages and other inflammatory cells, cell proliferation in lung epithelium, and the presence of dust in the interstitium and lymphatics.…”
Section: Criteria For Establishing the Mtd In Fiber Inhalation Studiesmentioning
confidence: 99%